Availability of family care resources, type of primary caregiving and home death among the oldest-old: A population-based retrospective cohort study in China - Zihui Xiong; Weiyan Feng; Zhong Li (Elsevier, 2022)
Place of death is one of the quality indicators for end-of-life (EOL) care, and most people prefer to die at home. This study investigated the association between availability of family care resources, type of primary caregiving and home death. A sample of 21,677 deceased oldest-old consisting of 5,224 octogenarians, 8,489 nonagenarians, and 7,964 centenarians, was derived from the 1998-2018 Chinese Longitudinal Healthy Longevity Survey. Marital status, number of children and living with family members were indicators for the availability of family care resources. After accounting for other covariates, number of children (4-6 vs. 0-3: adjusted odds ratio [95% CI]: 1.81 [1.54 to 2.13]; >6 vs. 0-3: 2.63 [2.09 to 3.31]) and living with family members (28.29 [23.89 to 33.49]) were positively associated with informal caregiving (all P < 0.001). Number of children (4-6 vs. 0-3: 1.17 [1.04 to 1.32]; >6 vs. 0-3: 1.19 [1.03 to 1.38]), living with family members (2.52 [2.17 to 2.92]) and informal caregiving (11.43 [9.58 to 13.64] were associated with increased odds of dying at home (all P < 0.05). The association between availability of family care resources (number of children: β [95% CI], % mediated: 0.05 [0.04 to 0.07], 55.6%; living with family members: 0.14 [0.13 to 0.15], 46.7%) and home death was partially mediated by the type of primary caregiving. Our results suggest that the availability of family care resources played a significant role in making home death possible through informal caregiving. Therefore, continuous policy efforts on the different roles of specific family care resources are warranted to train and support family caregivers to facilitate culturally appropriate EOL services, such as dying at preferred place.